Poverty in Canada and the USA: Measurement, Trends and Implications - Lars Osberg (Luxembourg Income Study (LIS), 2000)
This paper begins by asking how poverty in affluent countries should be measured, before examining recent evidence on poverty intensity and its social significance. Section 1 advocates use of the Sen-Shorrocks-Thon index of poverty intensity and introduces the 'Poverty Box' as a summary graphical representation. Recently, poverty intensity has increased in Canada while falling in the US. Although on a national basis Canadian poverty intensity remained below that in the US, by 1997 many US states were indistinguishable from Canadian provinces. Fixed effects regressions across states and provinces using Generalized Least Squares and bootstrap standard errors indicate that changes in the unemployment rate, unemployment insurance and social assistance are significant determinants of changes in poverty intensity. Since changes in trade exposure were not statistically significant, the general moral is that trade liberalization does not preclude the macro economic and social policy choices which can improve poverty outcomes. The paper concludes with a discussion of the social significance of income poverty, and its relationship to social exclusion and fundamental human rights.
Keywords: 330; Armut; Messung; Sozialer Indikator; Räumliche Verteilung; USA; Kanada